Identification and evolution of nsLTPs in the root nodule nitrogen fixation clade and molecular response of Frankia to AgLTP24 - Mélanie Gasser; Jean Keller; Pascale Fournier; Petar Pujic; Philippe Normand; Hasna Boubakri (Scientific Reports, 2023)
Abstract Non-specific lipid transfer proteins (nsLTPs) are antimicrobial peptides, involved in several plant biological processes including root nodule nitrogen fixation (RNF). Nodulating plants belonging to the RNF clade establish symbiosis with the nitrogen-fixing bacteria rhizobia (legumes symbiosis model) and Frankia (actinorhizal symbiosis model) leading to root nodule formation. nsLTPs are involved in processes active in early step of symbiosis and functional nodule in both models. In legumes, nsLTPs have been shown to regulate symbiont entry, promote root cortex infection, membrane biosynthesis, and improve symbiosis efficiency. More recently, a nsLTP, AgLTP24 has been described in the context of actinorhizal symbiosis between Alnus glutinosa and Frankia alni ACN14a. AgLTP24 is secreted at an early step of symbiosis on the deformed root hairs and targets the symbiont in the nitrogen-fixing vesicles in functional nodules. nsLTPs are involved in RNF, but their functions and evolutionary history are still largely unknown. Numerous putative nsLTPs were found up-regulated in functional nodules compared to non-infected roots in different lineages within the RNF clade. Here, results highlight that nodulating plants that are co-evolving with their nitrogen-fixing symbionts appear to have independently specialized nsLTPs for this interaction, suggesting a possible convergence of function, which opens perspectives to investigate nsLTPs functions in RNF.